Scientific And Methodological Foundations For Assessing The Level Of Formation Of Affective-Emotional Intelligence Based On Working With Literary Works - Jamalova Kamola Shaxabiddinovna (International Scientific and Current Research Conferences, 2026)
This article highlights the scientific and methodological foundations for assessing the level of formation of affective-emotional intelligence of primary school age pupils based on working with literary works. The structural components of affective-emotional intelligence, the criteria for identifying them, indicators and assessment levels are analyzed. In addition, the methods and techniques of conducting diagnostics based on literary texts, as well as the possibilities of identifying pupils’ empathy, skills of understanding and managing emotions, and reflection are revealed. The research results show that systematic work with literary works makes it possible not only to develop affective-emotional intelligence, but also to reliably assess the level of its formation.